2013
DOI: 10.2108/zsj.30.1038
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Thermal Effects on Embryonic Cells of Endangered Hawksbill TurtleEretmochelys imbricata

Abstract: The hawksbill turtle is an ectotherm, whose sex is determined by temperature during embryonic development. This study aimed to determine whether embryonic hawksbill turtle cells respond differently to temperature than mammalian cells. Embryonic hawksbill turtle cells were established in culture, and thermal effects on these cells were investigated in vitro. Cells were maintained in Dulbecco's Modified Eagle Medium supplemented with non-essential amino acids, vitamin solution, sodium pyruvate, and 10% fetal bov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Previous literature suggests that temperatures at or slightly above the source animals’ preference are suitable for reptilian cell culture work and that an optimal temperature would occur between approximately 23 and 37 °C for sea turtles. Our findings indicated that 30 °C is the preferred growth temperature for primary loggerhead fibroblast sea turtle skin cultures and corresponds to the 28–30 °C rearing temperature at the NOAA Sea Turtle Facility. Immortal green sea turtle cells are reported to grow well at 25–30 °C, primary hawksbill and olive ridley sea turtle cells at 26 °C, and loggerhead sea turtle leukocytes at 30 °C, though proliferation was reported at a wide range of other temperatures. ,,, ,, …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous literature suggests that temperatures at or slightly above the source animals’ preference are suitable for reptilian cell culture work and that an optimal temperature would occur between approximately 23 and 37 °C for sea turtles. Our findings indicated that 30 °C is the preferred growth temperature for primary loggerhead fibroblast sea turtle skin cultures and corresponds to the 28–30 °C rearing temperature at the NOAA Sea Turtle Facility. Immortal green sea turtle cells are reported to grow well at 25–30 °C, primary hawksbill and olive ridley sea turtle cells at 26 °C, and loggerhead sea turtle leukocytes at 30 °C, though proliferation was reported at a wide range of other temperatures. ,,, ,, …”
Section: Discussionmentioning
confidence: 99%
“…Immortal green sea turtle cells are reported to grow well at 25−30 °C, primary hawksbill and olive ridley sea turtle cells at 26 °C, and loggerhead sea turtle leukocytes at 30 °C, though proliferation was reported at a wide range of other temperatures. 12,21,33,[22][23][24][25]29,31 Reptilian cell cultures reported in the literature utilized cell medium designed for mammalian cells. Multiple options have been examined for sea turtle cell cultures, including medium 199, minimum essential medium (MEM), Dulbecco's modified Eagle medium (DMEM), Leibovitz L-15, F-10 nutrient mix, F-12 nutrient mix, basal medium Eagle (BME), and RPMI 1640.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation